The indications level of bankruptcy by Altman Z-Score calculation method (case study on subsidiaries of PT Kereta Api Indonesia Persero) - Rizkiansyah, Agung; Falikhatun, Falikhatun (Management and Entrepreneurship: Trends of Development, 2021)
This study aims to observe the condition of several companies that are affiliated as subsidiaries of PT Kereta Api using the Altman Z-Score to predict the indication of bankruptcy. The indication of bankruptcy is a way to the company to make a decision regarding the strategy that needs to be taken. In this research, the indication of bankruptcy commonly used the category that is included in the Altman Z score model. This includes quantitative research with a goal to detect and analyze the object of the research which is based on the secondary subject of Financial Reporting about the sign of bankruptcy of the company by using Altman Z-Score model. This research method used descriptive and quantitative approach. The research results show that from six Subsidiaries Companies of PT Kereta Api Indonesia (Indonesian railway companies) that are analyzed as the sample in this research, there are 3 companies that are regarded as “healthy companies” (companies that has a stable condition), a company that is included in grey area (predicted to experience a bankruptcy) and two companies that are included in more dangerous area or indicated as companies that have almost experienced a bankruptcy.JEL Classification: C63, D59, G33.